2014
DOI: 10.5231/psy.writ.2015.3006
|View full text |Cite
|
Sign up to set email alerts
|

Discordancia de peso al nacer en gemelos: consecuencias y su perdurabilidad en el desarrollo psicológico

Abstract: Cada vez nacen más gemelos con discordancia de peso intrapar, factor de riesgo que puede afectar su desarrollo, especialmente el del hermano de menor peso intrapar. Sin embargo, pocos estudios abordan sus posibles disfunciones más allá de las obstétricas; de modo que el conocimiento acerca de las consecuencias de la discordancia de peso intrapar en su desarrollo psicológico es escaso. Este trabajo revisa la literatura y recapitula las consecuencias de la discordancia de peso intrapar en el desarrollo psicológi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…This twin is usually the most affected since they have a less optimal intra-uterine environment than their heavier birth weight twin, which ultimately affects both their birth weight and brain development [36][37][38][39]. Among other disadvantages the lighter twins face, the literature on the subject has shown that they have lower IQ; perform significantly worse in cognition, language, and motor skills compared to the heavier twins; and are usually at major risk for later behavior problems [37][38][39][40]. However, many aspects of these children's development are still unknown because, if we consider that the research on psychoeducational issues in twin children is scarce, even scarcer is the research focused on twin children with BWD.…”
Section: Twin Babies In Early Childhood Educationmentioning
confidence: 99%
“…This twin is usually the most affected since they have a less optimal intra-uterine environment than their heavier birth weight twin, which ultimately affects both their birth weight and brain development [36][37][38][39]. Among other disadvantages the lighter twins face, the literature on the subject has shown that they have lower IQ; perform significantly worse in cognition, language, and motor skills compared to the heavier twins; and are usually at major risk for later behavior problems [37][38][39][40]. However, many aspects of these children's development are still unknown because, if we consider that the research on psychoeducational issues in twin children is scarce, even scarcer is the research focused on twin children with BWD.…”
Section: Twin Babies In Early Childhood Educationmentioning
confidence: 99%